O conceito de ansiedade na análise do comportamento - COÊLHO, Nilzabeth Leite (Universidade Federal do Pará, 2011)
Issues concerning to anxiety have been discussed in Psychology focusing several different aspects, but definitions of anxiety are far from consensual. The difficulty is due to several reasons, among which is the lack of a precise reference to behavioral relations. Divergence is also found in behavior-analytic literature. Some accounts stress the role of direct contingencies in controlling patterns of anxiety responses. Other definitions approach verbal aspects as possible sources of additional control. In the late accounts, the multiple functions of ones self-descriptive reports and also the semantic conditioning have been pointed out as possible explanations. In the present work, 47 papers were examined in the behavior-analytic literature in order to identify the types of behavioral relationships that are being suggested in the different uses of the concept of anxiety in the Behavior Analysis and the (in)compatibility of those approaches. The study took as reference categories of register that refer to what each author says in terms of respondent, not verbal operant, verbal operant components, and intervention perspectives. A more qualitative analysis was carried out with the use of analytical categories that refer to (1) the role performed by the physiologic alterations in the definition of anxiety; (2) the verbal and nonverbal operant relations involved in the phenomenon, and (3) the implications of each one of those analyses to a face-to-face verbal therapy. This exam made possible the identification of variations in the definitions concerning to (1) the type of behavioral relations involved; (2) the arrangement of contingencies that produce those relations; (3) the corporeal conditions produced concomitantly by the same contingencies; (4) to the functions of those corporeal conditions in the behavioral relations, and (5) the processes through which verbal stimuli participate in those relations. However, those variations in the definition can be understood as complementary analyses not incompatible with each other. The explanation of behavioral phenomenon based on a complexity continuum can be a model capable of joining those variations, making possible an understanding of (1) the relational network that can take place in an instance of anxiety, as well as (2) the function carried out by each one of the components in the anxiety.